Social Roles of Grandparents in an Ageing, Modern Society - Dorota Szaban; Beata Trzop (Jesuit University Ignatianum in Krakow, 2021)
RESEARCH OBJECTIVE: The authors' aim is to create an original typology of the social roles of grandparents in modern society. The reflection is set in the context of demographic changes related to ageing processes and theories of life cycles. THE RESEARCH PROBLEM AND METHODS: The main thesis is that despite the significant sociocultural changes occurring in the context of the intensifying aging processes of societies, it is possible to indicate the multiplicity of roles played by grandparents. The article is based on two research projects conducted among women aged 50‑64 and men aged 55‑69 living in the Lubuskie Voivodeship. The data used has a qualitative character, and the empirical basis is 110 written biographical stories. THE PROCESS OF ARGUMENTATION: The background of the study is data from public statistics that illustrate the deepening ageing processes of the region's population. Unfavourable demographic processes are intertwined with sociocultural changes related to the change of gender roles, professional activity, and free time. This element is related to the concept of life phases. An extensive theoretical introduction precedes the analysis of the results of research on the typology of the social roles of women and men as grandparents. RESEARCH RESULTS: An original typology of the roles of grandparents in the modern world was proposed. The mechanisms related to the roles focus mainly on meeting the needs of the family in the first place. We can draw an axis of traditional vs. modern, which leaves room for some other indirect possibilities (e.g. space for female self‑realization). However, it depends on the sociocultural factors and scripts implemented at earlier stages of family life. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: There is no uniform and coherent grandfathering pattern, and there is a clear difference between the sexes on the axis of involvement in caring functions.